Biodiversity dynamics : turnover of populations, taxa, and communities - McKinney, Michael L.; Drake, James A., 1954- (Columbia University Press, 1998)
How will patterns of human interaction with the earth's eco-system impact on biodiversity loss over the long term--not in the next ten or even fifty years, but on the vast temporal scale be dealt with by earth scientists? This volume brings together data from population biology, community ecology, comparative biology, and paleontology to answer this question.